Managing Political Information: A Malaysian Perspective - Ahmad, Jamilah (Jurnal Ilmu Sosial dan Ilmu Politik, 2010)
In the development of democratization and the expression of civil and political rights of Malaysian citizens, the pattern of control developed by the regime that is currently in power (Barisan Nasional) for the last 50 years in the mass media began to reap the resistance and tend to be ineffective. Malaysian citizens began to demand the Malaysian government to change the pattern of political information management. In addition, the mass media alone is expected to play a more significant role as an intermediary agent in supporting the process of transparency and accountability of government policy. This article shows that the openness of public information is a prerequisite for political democracy in Malaysia to help the government minimize the mis-management of governance policies, especially in finance and resource management.